Luteal Lipids Regulate Progesterone Production and May Modulate Immune Cell Function During the Estrous Cycle and Pregnancy - Hughes, Camilla H. K.; Bosviel, Remy; Newman, John W.; Pate, Joy L. (Frontiers in Endocrinology, 2019)
Although the corpus luteum (CL) contains high concentrations of lipid in the form of steroid hormone precursors and prostaglandins, little is known about the abundance or function of other luteal lipid mediators. To address this, seventy-nine lipid mediators were measured in bovine CL, using ultra performance liquid chromatography-tandem mass spectrometry. CL from estrous cycle days 4, 11, and 18 were compared and, separately, CL from days 18 of the estrous cycle and pregnancy were compared. Twenty-three lipids increased as the estrous cycle progressed (P < 0.05), with nine increasing between days 4 and 11 and fourteen increasing between days 4 and 18. Overall, this indicated a general upregulation of lipid mediator synthesis as the estrous cycle progressed, including increases in oxylipins and endocannabinoids. Only 15-KETE was less abundant in the CL of early pregnancy (P < 0.05), with a tendency (P < 0.10) for four others to be less abundant. Notably, 15-KETE also increased between estrous cycle days 4 and 18. Ingenuity Pathway Analysis (IPA, Qiagen) indicated that functions associated with differentially abundant lipids during the estrous cycle included leukocyte activation, cell migration, and cell proliferation. To investigate changes in CL during maternal recognition of pregnancy, this lipid dataset was integrated with a published dataset from mRNA profiling during maternal recognition of pregnancy. This analysis indicated that lipids and mRNA that changed during maternal recognition of pregnancy may regulate some of the same functions, including immune cell chemotaxis and cell-cell communication. To assess effects of these lipid mediators, luteal cells were cultured with 5-KETE or 15-KETE. One ng/mL 5-KETE reduced luteal progesterone on day 1 of culture, only in the absence of luteinizing hormone (LH), while 1 ng/mL 15-KETE induced progesterone only in the presence of LH (10 ng/mL). On day 7 of culture, 0.1 ng/mL 15-KETE reduced prostaglandin (PG)F2A-induced inhibition of LH-stimulated progesterone production, while 1 ng/mL 15-KETE did not have this effect. Overall, these data suggest a role for lipid mediators during luteal development and early pregnancy, as regulators of steroidogenesis, immune cell activation and function, intracellular signaling, and cell survival and death.